Bolusing frequency and amount impacts glucose control during hybrid closed‐loop. Issue 3 (19th August 2017) - Bally, L.; Thabit, H.; Ruan, Y.; Mader, J. K.; Kojzar, H.; Dellweg, S.; Benesch, C.; Hartnell, S.; Leelarathna, L.; Wilinska, M. E.; Evans, M. L.; Arnolds, S.; et al.
Abstract: Aim: To compare bolus insulin delivery patterns during closed‐loop home studies in adults with suboptimally [HbA1c 58–86 mmol/mol (7.5%–10%)] and well‐controlled [58 mmol/mol (< 7.5%)] Type 1 diabetes. Methods: Retrospective analysis of daytime and night‐time insulin delivery during home use of closed‐loop over 4 weeks. Daytime and night‐time controller effort, defined as amount of insulin delivered by closed‐loop relative to usual basal insulin delivery, and daytime bolus effort, defined as total bolus insulin delivery relative to total daytime insulin delivery were compared between both cohorts. Correlation analysis was performed between individual bolus behaviour (bolus effort and frequency) and daytime controller efforts, and proportion of time spent within and below sensor glucose target range. Results: Individuals with suboptimally controlled Type 1 diabetes had significantly lower bolus effort ( P = 0.038) and daily bolus frequency ( P < 0.001) compared with those with well‐controlled diabetes. Controller effort during both daytime ( P = 0.007) and night‐time ( P = 0.005) were significantly higher for those with suboptimally controlled Type 1 diabetes. Time when glucose was within the target range (3.9–10.0 mmol/L) during daytime correlated positively with bolus effort ( r = 0.37, P = 0.016) and bolus frequency ( r = 0.33, P = 0.037). Time when glucose was below the target range during daytime was comparable in both groups ( P = 0.36), and did not correlate significantly with bolus effort ( r = 0.28, P = 0.066) or bolus frequency ( r = –0.21, P = 0.19). Conclusion: More frequent bolusing and higher proportion of insulin delivered as bolus during hybrid closed‐loop use correlated positively with time glucose was in target range. This emphasises the need for user input and educational support to benefit from this novel therapeutic modality. What's new?: Glucose control during hybrid closed‐loop therapy is linked to bolusing behaviour. Closed‐loop users with well‐controlled Type 1 diabetes bolused more frequently without increasing the risk of hypoglycaemia. We highlight the importance of user input and education to gain optimal benefit from hybrid closed‐loop.